2007
DOI: 10.1002/mnfr.200600273
|View full text |Cite
|
Sign up to set email alerts
|

The influence of olive oil on human health: not a question of fat alone

Abstract: Olive oil is the most representative food in the traditional Mediterranean diet and its most important source of MUFA. The healthy benefits of MUFA-rich diets on plasma cholesterol levels, were the first to generate interest in this dietary model. In addition to the benefits conferred by its lipids, olive oil has other biological effects, some of them also related to MUFA. However, most recent studies have shown that there are a number of properties that depend on, or are potentiated by, the consumption of oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(161 citation statements)
references
References 86 publications
2
150
1
8
Order By: Relevance
“…Minor components (the unsaponifiable fraction) include aliphatic and triterpenic alcohols, sterols, hydrocarbons as squalene, volatile compounds, tocopherols, carotenes, chlorophyll and phenolic compounds (13)(14)(15) .…”
Section: Olive Oil Bioactive Componentsmentioning
confidence: 99%
“…Minor components (the unsaponifiable fraction) include aliphatic and triterpenic alcohols, sterols, hydrocarbons as squalene, volatile compounds, tocopherols, carotenes, chlorophyll and phenolic compounds (13)(14)(15) .…”
Section: Olive Oil Bioactive Componentsmentioning
confidence: 99%
“…Oleic acid [20] Inhibition of platelet aggregation and alteration of the platelet/vascular wall, reduction of fibrinogen, factor VII and the principal suppressant of hemostasis, thereby increasing fibrinolysis Phenolic compounds [44][45][46][47][48][49] Reduction of TXB2 and LTB4 in both hyperlipaemic subjects and patients with type 2 diabetes [44,50] Chemo-protective action and improvement of the endothelium function Phenolic compounds (hydroxytyrosol and tyrosol) [44,50] Preventive action against thrombotic and microthrombotic events in patients with type 2 diabetes and hyperlipaemic subjects Hydroxytyrosol [44,50] Reduction of risks for patients with cardiac pathologies [25] Oxidation and oxidative stress Maintenance of cellular integrity and reduction of ageing High level of oleic acid and lack of excess of linoleic acid [56] Anti-inflammatory and vasodilatative action a-linolenic acid (ALA) [60] Delay of atherosclerosis Phenolic compounds [16,44,59, 60] Prevention of oxidation of cells-membrane lipids and plasma lipoproteins, reducing the risk of atherosclerosis Tocopherols [43,60] Reduced production of free radicals and prevention of damages to the cellular membrane, mitochondria, and DNA, with beneficial effects on aging and cancer risk [66,67] Inflammation Anti-inflammatory action by non-selectively inhibition of the COX-1 and COX-2 enzymes Oleocanthal [38,69] Protection against various pathological conditions (10 types of tumors including colon, stomach, breast, prostate, lung, and Alzheimer's disease) Oleocanthal [72,73,78] Obesity and diabetes Reduction of risk by inhibition of the activation of NF-kB at the cellular level Phenols, carotenoids, and tocopherols [60,92] Protective action on mitochondria, reduced production of free radicals and protection against DNA oxidation [60,…”
Section: Towards Evidence-based Medicinementioning
confidence: 99%
“…Recently, a review pointed out that adequate compliance with the MD can reduce mortality due to cardiovascular disease by 9%, cancer by 6%, total mortality by 9% and the incidence of Parkinson's and Alzheimer's disease by 13% [19]. Concerning with the lipoprotein profile, it is well known that the LDL cholesterol is decreased when EVOO substitutes the same caloric value of the saturated fat, leaving the HDL level unaltered, while if the caloric value is too high in carbohydrates, it leads to a reduction in triglyceridemia and an increase in HDL [25,26]. In reality, some of the results reported can be partially obtained with any type of oil that contains high quantities of oleic acid, following genetic modifications in plants, although it has been demonstrated that in humans the better results are due to the combined action of oleic acid and EVOO minor compounds, such as some phenols.…”
Section: Towards Evidence-based Medicinementioning
confidence: 99%
See 2 more Smart Citations